Resurrection and redefinition of the genus Tubella (Porifera: Spongillidae) with a worldwide list of valid species - Pinheiro, Ulisses; Nicacio, Gilberto (Zootaxa, 2012)
The confusion about the genus Tubella began when Carter (1881) relocated three species described by Bowerbank (1863)—Spongilla paulula; Spongilla reticulata and Spongilla recurvata to the genus Tubella, and also described Tubella spinata. However, Carter ignored Gray (1867) who proposed the genus Metania for S. reticulata and S. paulula, and Acalle for S. recurvata. Later, Vejdovsky (1888) described the genus Trochospongilla comprising species which have only one type of megasclere, without microscleres and birotulate gemmoscleres with rotules that may have unequal size. These features were congruent with some species of Tubella. After seven decades, De Laubenfels (1936) returned to the classification proposed by Gray (1867) concerning the genus Metania. On occasion, De Laubenfels proposed types species, designating Spongilla reticulata Bowerbank, 1863 for the genus Metania, and Tubella paulula Bowerbank, 1863 (misspelled as Tubella paulata) for the genus Tubella. Thus, Trochospongilla should be considered a junior synonym of Tubella but unfortunately this did not happen. Penney & Racek (1968) complicated this scenario when they recommended that the genus Tubella should be removed from the sponge classification, since it would be a conglomerate of several species belongin to different genera. This recommendation has been followed by recent authors, and the genus Tubella is commonly referred as a synonym of the genera Acalle, Metania and especially Trochospongilla. In order to correct this taxonomic misconception, we propose here the revalidation and redefinition of genus Tubella.